The impact of public art education on college students’ mental health literacy - Zhang, Shengyu; Zhao, Lege (Frontiers in Public Health, 2024)
This study aims to explore the impact of public art education on the mental health literacy of College Students. Conducted over a four-month period, the intervention involved freshmen from a Chinese college, comparing 1334 students in the experimental group with 1139 in the control group. Data were collected through a self-developed questionnaire and a standardized mental health literacy scale before and after the intervention. Results showed that the experimental group's overall mental health literacy score significantly increased from 64.051 pre-intervention to 79.260 post-intervention, while the control group showed no significant changes during the same period. The experimental group demonstrated significant improvements in their ability to identify psychological disorders, belief in receiving professional help, attitudes towards seeking appropriate help, and knowledge in seeking mental health information. Furthermore, the frequency of classroom interaction was positively correlated with improvements in mental health literacy (regression coefficient = 2.261***), highlighting the critical role of active participation in public art education settings. This study underscores the importance and effectiveness of implementing public art education in higher education and provides empirical support for future educational policies and practices. 2Entering college is a critical transition for young students, marked by challenges like academic pressures, social relationships, and self-identity exploration, which can lead to psychological issues such as anxiety and depression (Robinson et al., 2021). Enhancing mental health literacy among college freshmen is therefore essential (Campbell et al., 2022 ;Ruiz-Aranda et al., 2012). Mental health literacy, as defined by Jorm et al., involves not only basic knowledge of mental health but also the skills to identify, manage, and seek professional help for psychological issues (Jorm et al., 1997). Research indicates that students with higher mental health literacy manage stress more effectively, exhibiting improved learning and social skills, which positively impacts their academic and personal development (